Overcoming Knowledge-Sharing Barriers that Affect Software Quality: An Experience Report - Lima, Rayfran Rocha; Ekwoge, Oswald; Bonifácio, Bruno; Cunha, Raquel; Barbosa, Hualter; Rocha, Ana Carolina Oran (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2021)
There are several barriers to the knowledge management process in the current technological market environment that can affect software quality, especially in a distributed environment. One of them relates to the knowledge sharing needed to fulfill required tasks to ensure the projects’ deliverables. This paper is an experience report that assesses the gaps of knowledge (GoK) in the project leaders (PL) team. To accomplish this, it was carried out documental analysis and focus group sessions to review essential activities developed by the PL team during the software development process. Afterward, we carried out a survey to verify the GoK of PL team members related to their ability to perform essential activities to develop Security Maintenance Release projects. This paper also shows analyzes of three ways to share knowledge and a training program guidelines to eliminate existing GoK in the PL team. The findings reveal that although many factors affect the success rates of the knowledge sharing process, a training plan considering the combination of four factors can shorten the learning curve of PL team members. We hope this paper can contribute helping other knowledge-based companies and scientific community to increase their competitive advantages related to the knowledge sharing process and to minimize software quality problems such as rework effort and defective product delivery.